Study of Enzymatic Activity for The Detection of Bacteria in Seawater in Iraq: Studi Aktivitas Enzim untuk Deteksi Bakteri dalam Air Laut di Irak - Al-Taie, Raqiya Khudhur Abbas; Al-Baky , Rasha Khalid Abd (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Monitoring bacterial contamination in seawater is essential for environmental safety, as fecal coliforms like Escherichia coli pose serious health risks. Specific Background: Traditional culture-based methods often underestimate bacterial viability, particularly in stressed or non-cultivable states, limiting their reliability. Knowledge Gap: Limited studies have explored how enzymatic activity can persist in non-cultivable bacteria and how it may be applied as a sensitive detection tool in marine environments. Aims: This study aimed to assess the persistence of β-galactosidase and β-glucuronidase activity in E. coli under varying stress conditions, including chlorine exposure, temperature, antibiotic treatment, and freeze-thaw cycles, to evaluate their potential as indicators of bacterial survival in seawater. Results: The findings revealed that under severe treatments (chlorine, high temperature), enzymatic activity declined simultaneously with cultivability, whereas under milder stress (chloramphenicol, freeze-thaw), enzymatic activity persisted despite significant loss of cultivability. Comparative modeling and docking analyses confirmed the structural and functional properties of β-galactosidase relevant to bacterial adaptation. Novelty: This research demonstrates that enzymatic activity may serve as a marker for viable but non-cultivable bacteria, bridging the gap between culture-based detection and molecular approaches. Implications: These results provide a foundation for developing rapid, sensitive monitoring tools for marine water quality, enhancing early detection of fecal contamination.Highlight : Enzymatic activity is used to assess bacterial viability in different stress conditions. Severe treatments cause simultaneous loss of cultivability and enzymatic activity. Mild treatments reduce cultivability more than enzymatic activity, indicating partial persistence. Keywords : Enzymatic Activity, Bacteria, Freeze-Thaw Cycles, Chloramphenicol, Seawater